Comparative efficacy of melatonin in attenuation of endotoxin/LPS induced hepatotoxicity in BALB/c mice - Khan, Ammara; Afzal, Ayesha; Rauf, Abdul; Waheed, Akbar (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Sepsis is characterized by overwhelming surge of cytokines and oxidative stress to one of many factors, gram negative bacteria commonly implicated. Despite major expansion and elaboration of sepsis pathophysiology and therapeutic approach; death rate remains very high in septic patients due to multiple organ damage including hepatotoxicity. The present study was aimed to ascertain the adequacy of melatonin (10mg/kg i.p), and its comparability with dexamethasone (3mg/kg i.p), delivered separately and collectively in endotoxin induced hepatotoxicity. Methods: The number of animals in each group was six. Endotoxin/LPS induced hepatotoxicity was reproduced in mice by giving LPS of serotype E. coli intraperitoneally. Preventive role was questioned by giving the experimental agent half an hour prior to LPS injection whereas therapeutic potential of the experimental agent was searched out via post LPS delivering. The extent of liver damage was adjudged via serum alanine aminotransferases (ALT) and aspartate aminotransferase (AST) estimation along with histopathological examination of liver tissue. Results: Melatonin was prosperous in aversion (Group 3) and curation (Group 4) of LPS invoked hepatotoxicity as evident by lessening of augmented ALT (≤0.01) and AST (≤0.01) along with restoration of pathological changes on liver sections (p≤0.05). Dexamethasone given before (Group5) and after LPS (Group 6) significantly (p≤0.05) attenuated LPS generated liver injury. Combination therapy with dexamethasone in conjunction with melatonin (Group 7) after LPS administration tapered LPS evoked hepatic dysfunction statistically considerably, however the result was comparable to single agent therapy. Conclusions: Melatonin set up promising results in endotoxin induced hepatotoxicity and can be used therapeutic adjuncts to conventional treatment strategies in sepsis induced liver failure. Combination therapies however generated no synergistic results.